INTERACTIVE LEARNING METHODS IN HIGHER EDUCATION INSTITUTIONS - Marchenko, Nataliia; Slipchuk, Valentyna; Yuzkiv, Halyna (The Modern Higher Education Review, 2023)
The article is devoted to the actual problem of using interactive learning methods in the educational process in institutions of higher education. Attention is focused on the fact that student-centred learning requires teachers to use innovative methods that ensure the maximum connection of theoretical information with its practical application, and the development of professional skills by directly solving cases and problem situations. With this in mind, the authors analysed some modern methods of interactive learning and found that a characteristic feature of modern higher education is the development of students' critical thinking using such methods as ‘Fishbone’, Bloom's daisy and cube, and Brainstorming. It was determined that an integral component of the modern educational process is the use of various digital applications that help the teacher to develop interesting lessons. Usually, they are aimed at solving several tasks: gamification of learning, consolidation of learned material and evaluation of learning results. The tutorial was analysed as an interactive form of independent work. It is aimed at in-depth familiarization of students with the studied subject, discussion of creative projects during classes and development of creative potential. This form of independent student work allows you to teach them to think, for example, to synthesize various sources, formulate their own theses and prove them, anticipate criticism of their arguments and answer questions. At the same time, the authors emphasize that active methods should be organically combined with passive ones. In view of this, the teacher should carefully consider the procedure for using traditional and interactive teaching methods, not to abuse a significant number of the latter, as this can lead to a decrease in motivation.